2023
DOI: 10.1111/1759-7714.14895
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term outcomes of robotic lobectomy versus video‐assisted lobectomy in patients with pulmonary neoplasms

Abstract: Background To explore whether robotic lobectomy (RL) is superior to video‐assisted lobectomy (VAL) in terms of short‐term outcomes in patients with pulmonary neoplasms. Methods From January 30, 2019 to February 28, 2022, a series of consecutive minimally invasive lobectomies were performed for patients with pulmonary neoplasms. Perioperative outcomes such as operation time, blood loss, dissected lymph nodes (LNs), surgical complications, postoperative pain control, length of postoperative stay in hospital, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
(139 reference statements)
3
6
0
Order By: Relevance
“…Three studies showed the need for transfusions in Robotic procedures is lower than in VATS (Adams et al, 1990;Kneuertz et al, 2019;Sun et al, 2023). The meta-analysis results (see Fig 4) confirm a significant difference in transfusion requirements between Robotic and VATS procedures (OR = 0.50; 95% CI: 0.27 -0.92), with low heterogeneity (I2: 6%; p = 0.34).…”
Section: Transfusion Ratementioning
confidence: 67%
See 2 more Smart Citations
“…Three studies showed the need for transfusions in Robotic procedures is lower than in VATS (Adams et al, 1990;Kneuertz et al, 2019;Sun et al, 2023). The meta-analysis results (see Fig 4) confirm a significant difference in transfusion requirements between Robotic and VATS procedures (OR = 0.50; 95% CI: 0.27 -0.92), with low heterogeneity (I2: 6%; p = 0.34).…”
Section: Transfusion Ratementioning
confidence: 67%
“…Among the 8 studies we identified, 6 studies reported data on the duration of surgery for Robotic Lobectomy and VATS. Four studies indicated that Robotic Lobectomy required a longer duration compared to VATS (Adams et al, 1990;Louie et al, 2016;Swanson et al, 2014;Terra et al, 2022), while 2 other studies showed that VATS procedures took longer than Robotic Lobectomy (Kneuertz et al, 2019;Sun et al, 2023). Based on the results of the metaanalysis (see Fig 3), no significant difference was found in the parameter of surgical duration between robotic and VATS procedures (OR 12.57, 95% CI [-6.64, +31.78]), with heterogeneous data (I2: 97%; p < 0.0001).…”
Section: Duration Of Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we believe that more studies are essential to define robotic surgical techniques, their feasibility, and outcomes in mediastinal tumour resection, especially when using prospectively collected data. Our previous studies demonstrated that the robotic portal approach using CO 2 insufflation could flatten the learning curves and have satisfactory short-term outcomes in lung resections for lung cancer patients [ 12 – 15 ], and was feasible in resection of the challenging mediastinal tumour in technique point of view from a case report [ 16 ]. Herein, we designed a prospective observational study that included a series of consecutive patients with mediastinal tumours who underwent robotic portal resections (RPRs) by a single surgical team, with the purpose of further determine the effectiveness and feasibility of the robotic portal approach for minimally invasive resection of a variety of mediastinal tumours in a real-world practice by a single robotic surgical team, and to provide a comprehensive overview of its utility across different mediastinal regions.…”
Section: Introductionmentioning
confidence: 99%
“…Strengths of this study include the fact that transfusion rates and risk factors for transfusions are on par with findings from recent cohort studies regarding RBC transfusion practices in thoracic surgery ( 13 - 16 ). Moreover, this study demonstrates what transfusion needs are in a “real-world” contemporary cohort where management practices are aligned with current recommendations for patient blood management.…”
mentioning
confidence: 99%